Air pollution influences the incidence of otitis media in children: A national population-based study - Park, Mina; Han, Jiyeon; Jang, Myoung-jin; Suh, Myung-Whan; Lee, Jun Ho; Oh, Seung Ha; Park, Moo Kyun (PloS one, 2018)
Otitis media (OM) is a major reason for children's visits to physicians and a major cause of their being treated with antibiotics. It not only causes economic burdens but also influences hearing, speech, and education. To our knowledge, no nationwide population-based study has assessed the association between air pollution and OM. Therefore, this study evaluated the association between air pollution levels and the incidence of OM. We identified cases of OM that occurred in South Korea between January 2011 and December 2012 from the Korea National Health Insurance Service-National Sample Cohort database, and evaluated its relationship with five air pollutants: particulate matter (PM10, particulates ≤10 μm in diameter), nitrogen dioxide (NO2), ozone (O3), sulfur dioxide, and carbon monoxide. Associations between the weekly incidence of OM and the five air pollutants were analyzed using generalized estimating equations. Conditional logistic regression analysis was used to obtain odds ratios (ORs) and their 99.9% Bonferroni-corrected confidence intervals after adjusting for gender, age, season, and region. We based our analysis on 160,875 hospital visits for OM by children aged <15 years. Correlations with higher concentrations of the five pollutants showed higher ORs than did the reference values at most time lags. PM10 had the largest influence on the OM incidence at a time lag of 0 weeks, whereas NO2 and O3 had the largest impacts on OM incidence at time lags of 1 and 4 weeks, respectively. These findings support the notion that the incidence of OM is associated with ambient air pollution.